Basophil activation test shows high accuracy in the diagnosis of peanut and tree nut allergy: The Markers of Nut Allergy Study. Issue 6 (29th December 2020) - Duan, Lucy; Celik, Alper; Hoang, Jennifer A.; Schmidthaler, Klara; So, Delvin; Yin, Xiaojun; Ditlof, Christina M.; Ponce, Marta; Upton, Julia E.M.; Lee, Jean‐Soo; Hung, Lisa; Breiteneder, Heimo; et al.
Abstract: Background: Peanut and tree nut allergies are the most important causes of anaphylaxis. Co‐reactivity to more than one nut is frequent, and co‐sensitization in the absence of clinical data is often obtained. Confirmatory oral food challenges (OFCs) are inconsistently performed. Objective: To investigate the utility of the basophil activation test (BAT) in diagnosing peanut and tree nut allergies. Methods: The Markers Of Nut Allergy Study (MONAS) prospectively enrolled patients aged 0.5–17 years with confirmed peanut and/or tree nut (almond, cashew, hazelnut, pistachio, walnut) allergy or sensitization from Canadian (n = 150) and Austrian (n = 50) tertiary pediatric centers. BAT using %CD63 + basophils (SSClow/CCR3pos) as outcome was performed with whole blood samples stimulated with allergen extracts of each nut (0.001‐1000 ng/mL protein). BAT results were assessed against confirmed allergic status in a blinded fashion to develop a generalizable statistical model for comparison to extract and marker allergen‐specific IgE. Results: A mixed effect model integrating BAT results for 10 and 100 ng/mL of peanut and individual tree nut extracts was optimal. The area under the ROC curve (AUROC) was 0.98 for peanut, 0.97 for cashew, 0.92 for hazelnut, 0.95 for pistachio, and 0.97 for walnut. The BAT outperformed sIgE testing for peanut or hazelnut and was comparable for walnut (AUROC 0.95, 0.94, 0.92) in a sub‐analysis in sensitized patients undergoing OFC. Conclusions: Basophil activation test can predict allergic clinical status to peanut and tree nuts in multi‐nut‐sensitized children and may reduce the need for high‐risk OFCs in patients. Abstract : BAT can predict allergic clinical status to peanut and individual tree nuts in multi‐nut‐sensitized children from Austria and Canada. Mixed effect model integrating 10 and 100 ng/mL of peanut and individual tree nut stimulation is effective in diagnosing allergy. BAT separates allergic from non‐allergic status in patients who underwent clinically indicated OFCs to peanut and individual tree nuts. Abbreviations: BAT, basophil activation test; OFC, oral food challenge; sIgE, specific IgE.